Self-help women organizations in Guinea Bissau: analysing economic and social impacts - Afonso, Aline (2015)
The main goal of this text is to enlighten the role of self-help women organizations in Guinea Bissau, emphasizing on the access of women and their families to health care. The economic instability caused by the economic liberalization process contributed to the increase of poverty and the reinforcement of the gender inequality in Guinea Bissau. The liberalization process was conducted in an uncontrolled way, without the State’s development of public policies capable to protect the human resources involved in this process, being the women the most affected. Inequality of opportunities, social inequality and discrimination against women undertake the development of the whole social, due to the women’s weight at all social levels. To Iman (1997)1 the study of women in general and African women in particular has contributed to broaden and deepen the knowledge about African realities. A more detailed knowledge of health care options for women and their choices in this sector is essential for the implementation of an effective health strategy coordinating both public health planning and the heterogeneous non-public sector.Deriving from the collected depositions in Guinea Bissau, the purpose of this article is, in the context of the economic liberalization process, to find an interpretation of the behaviours and survival strategies development by the women in the Mandjuandadi groups (leisure groups) and Abota groups (savings groups) to facilitate their access and their family access to the health services. As well as the aforementioned purpose, this text also intends to analyse these groups as a social and resilient space. The Abota, formed and managed by the women themselves, has revealed to be one of the most significant methods of mutual aid. These groups operate as an informal instrument of social protection, since the savings made by the group are regularly used to pay for domestic expenses, when they are unable to work due to medical reasons. It can also be used to buy medicines, pay for doctor’s consultations, and meet the expenses of children’s school tuitions and school gear. The Mandjuandadi groups are originally formed under the colonial rule as a form to resist to the cultural politics of the Portuguese. These groups was a free space to continue to sing, dance and play according to the Guinean manner (Semedo, 2010). We argue the practices utilized by the women in that groups are the principal way to guarantee their and their family access to the health services.